Fluorescence-free imaging and tracking of individual secretory proteins and bioparticles - Gemeinhardt, Andre; McDonald, Matthew P.; König, Katharina; Piliarik, Marek; Schaffer, Stefanie; Aigner, Michael; Mackensen, Andreas; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2017)
We apply interferometric scattering microscopy (iSCAT) to detect single label-free proteins down to a molecular size of 60 kDa. This technique allows us to investigate real-time insitusecretion of living cells.
CRIS-Team Scopus Importer:2023-03-27